Coumarin compounds against Alzheimer's disease: An in-silico approach - Mayra Avelar; Patricia Fernanda Delgado-Acosta; Ricardo Guzmán-Ávila; Virginia Flores-Morales (Results in Chemistry)
Alzheimer's disease, one of the most common causes of senile dementia, has no cure which makes the development of new treatments crucial. In this regard, secondary metabolites from plants have shown important bioactivity, including the inhibitory effect against acetylcholinesterase enzyme (AChE). An important group of such metabolites are coumarins, in particular the 7-hydroxycoumarin and its derivatives. These molecules have a wide variety of biological activities as antioxidants, anti-neurodegenerative and anti-Alzheimer drugs. In this study, eight coumarin derivatives were analyzed by means of ADMET properties, molecular docking and molecular dynamics simulations. Out of our set of derivatives, four coumarin compounds showed better docking scores (–11.60 to –12.07 kcal/mol) than the reference molecule donepezil, one of the drugs of first-line in the treatment of the disease as a reversible inhibitor of AChE. According to molecular dynamics simulations, the top selected compounds (Cou2, Cou5, Cou6 and Cou8) displayed interactions with amino acids from the binding site of AChE as potential multisite inhibitors, maintaining its interaction during the simulation time. The studied coumarins showed a biological activity as anti-inflammatory and free radical scavenger, regarding in silico predictions. All coumarins had good physicochemical and pharmacokinetic predicted parameters, thus positioned them as potential candidates to prove as Alzheimer's disease drugs by in vitro and in vivo evaluations.